Caracterização química de cromitas nos maciços de cromínia e mairipotaba, goiás, Brasil - Angeli, Nélson [UNESP]; Beltran Navarro, Guillermo Rafael [UNESP]; Farias Vlach, Silvio Roberto [UNESP]; Zanardo, Antenor (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2010)
Metaultramafic bodies tectonically emplaced within the metasedimentary sequence of the Araxá Group are associated with an ophiolitic melange in southeast Goiás. In the region of Crominia - Mairipotaba, they occur as lenticular bodies aligned E-W. Cumulate textures and geochemical data indicate that the parent rocks had harzburgitic to dunitic compositions. Relicts of primary crystals of olivine and orthopyroxene are suggestive of amphibolite facies metamorphic re-equilibration fabrics, even though the paragenesis and mineral associations of these metaultramafic rocks are typical of greenschist facies (T < 550°C and P = 5.5 kbar). The chromitites exhibit massive to breccioid structure and pull-apart texture, with chromite crystals around 0.5 mm in size. Chromite concentrations in the chromitite levels reach 70 to 85% by volume of the rock. The crystals are dispersed in the matrix, which is composed essentially of serpentine, and subordinately of chlorite and talc. The textures and geochemical data (Cr 2O 3 x TiO 2 and Mg x Cr ratios present in the chromitite) are similar to those observed in ophiolitic complexes. Hence, they correspond to allochthonous bodies (Alpine type) associated with an ophiolitic mélange.
Chemical characterization of chromite from the crominia and mairipotaba massifs, goiás, Brazil
Keywords: Araxá group; Brasilia belt; Chromite; Mineral chemistry; Ophiolitic melange; chemical composition; chromite; chromitite; concentration (composition); geochemistry; greenschist facies; melange; olivine; ophiolite; orthopyroxene; paragenesis; parent body; source rock; Brasilia Belt; Brazil; Goias